MOLECULAR MODELING AND STRUCTURAL ANALYSIS OF ARYLESTERASE OF ANCYLOSTOMA DUODENALE - SUBHAMAY PANDA; SANTAMAY PANDA; LEENA KUMARI (International Journal of Pharma and Bio Sciences, 2016)
Parasitic worm infection of humans is one of the most commonly prevalent helminth infection that has imposed great impact on society and public health in the developing world. The two species of hookworm, namely Ancylostoma duodenale and Necator americanus may be primarily responsible for causing parasitic infections in human beings. The highly prevalent areas for Ancylostoma duodenale infections are mainly India, Middle East, Australia, northern Africa and other parts of the world. The serum arylesterases/paraoxonases are family of enzymes that is involved in the hydrolysis of a number of organophosphorus insecticides to the nontoxic products. The participation of the enzymes in the breakdown of a variety of organophosphate substrates that is generally made up of paraoxon and numerous aromatic carboxylic acid esters (e.g., phenyl acetate), and hence combats the toxic effect of organophosphates. The aim of the present investigation is to evaluate the arylesterases of Ancylostoma duodenale giving special importance to structure generation, validation of the generated models, distribution of secondary structural elements and positive charge distribution over the structure. By the implementation of comparative modeling approach we propose the first molecular model structure of arylesterases of Ancylostoma duodenale.